Aplicação de silicato de potássio em coentro e cebolinha sobre estresse salino da solução nutritiva - Machado, Mateus Santos (2020)
Hydroponics is an important option for growing vegetables using brackish waters, especially in the semi-arid region; however, reductions in their productivity are evident, and studies are needed to mitigate these impacts. The objective of this work was to analyze the growth, yield and nutritional composition of coriander cv. Verdão and chives cv. Every year, grown in hydroponics, subjected to salinity levels of the nutrient solution with supplementary potassium silicate fertilization. The treatments were distributed in a randomized block design, consisting of six levels of electrical conductivities of the nutrient solution (2.3; 2.8; 3.3; 3.8; 4.3 and 4.8 dS m-1) for coriander and (2.3; 3.3; 4.3; 5.3; 6.3 and 7.3 dS m-1) for chives and two levels of potassium silicate (presence and absence) in a 6 x 2 factorial with four repetitions. The following characteristics of growth and yield were evaluated: plant height, absolute growth rate, relative growth rate, fresh and dry mass of the aerial part and root system, total water consumption, water use efficiency and nutrient content in aerial part. In the culture of coriander, fertilization with potassium silicate contributed significantly to the production characteristics, with an increase of 14.33 and 14.30% for fresh matter and roots respectively, in addition to reducing the levels of sodium and chlorine, thus contributing to reduction in damage caused by the respective ions. For the culture of chives there was no effect of the interaction between the factors for the characteristics studied. The use of potassium silicate increased the fresh matter mass of the crop by 19.18%. Therefore it was concluded that for the culture of coriander, fertilization with potassium silicate contributed to minimize the effect of salinity on plants under hydroponic conditions. In the culture of chives, fertilization with potassium silicate does not contribute to mitigate the impacts caused by salinity in addition to reducing the levels of chlorine in plants.